Effect of Source and Level of Vitamin D on the Performance of Breeder Hens and the Carryover to the Progeny - Coto, Cesar; Cerate, S.; Wang, Z.; Yan, F.; Min, Y.; Costa, F.P.; Waldroup, P.W. (International Journal of Poultry Science, 2010)
A study was conducted to evaluate the effect of the vitamin D level and source on the performance of broiler breeders and the deposition of this vitamin in egg yolk. Pullets reaching sexual maturity were depleted of vitamin D stores by feeding a vitamin D deficient diet during an eight week period. Following depletion, an experimental design was utilized consisting of a 5 x 2 factorial arrangement with four levels of dietary cholecalciferol (0, 300, 600, 1200 and 2400 IU/kg) and two levels of 25-hydroxycholecalciferol (25-OH, supplied as HyD) (0 and 68 μg/kg) for a total of 10 treatments. Each experimental diet was fed to two pens with 10 hens and 2 roosters that each received the experimental diets. Levels of 25-OH in plasma and in egg yolk were measured right after the depletion period and during the experimental phase. Performance parameters such as body weight, hen-day production, egg-shell thickness and egg mass were measured weekly. After the depletion period the level of 25-OH in plasma and egg yolk was below the detection limit confirming the depletion status. During the experimental phase the amount of 25-OH in plasma and egg yolk was higher as the cholecalciferol increased. When HyD was fed the level of 25-OH in plasma and egg yolk was higher than obtained when cholecalciferol was fed. Increasing levels of cholecalciferol improved egg shell thickness, hen-day production and egg mass. The addition of HyD improved egg-shell thickness, hen-day production and egg mass. The effect of HyD on performance was more noticeable at low levels of cholecalciferol with no difference at higher levels of cholecalciferol in the diet.